Inclusive Higher Education during the Covid-19 Pandemic - Zdravkova, Katerina; Krasniqi, Venera (Croatian Society for Information, Communication and Electronic Technology - MIPRO, 2021)
The Covid-19 pandemic caused a sudden shift towards online teaching, learning and assessment, which was troublesome for both teachers and students. The most affected were the students with various disabilities, whose inclusive options provided in the classroom were no longer available at home. Many socially responsible universities managed to support the education for differently abled students enabling various forms of alternative activities that partially or completely bypass their problems. This paper reviews the accessibility options of operating systems, learning management systems and especially assistive technologies that facilitate the education of impaired students. They cover the add-ons and tools for vision and hearing impairment. Teaching, learning and assessment are carefully examined for both disabilities. Particular attention is paid to practical work, which is a compulsory part of many higher education courses. The paper concludes with the major barriers of online higher education, which should during Covid-19 pandemic enable an equal right to all the students, regardless of their physical and mental disabilities.
Keywords: accessibility; assistive technologies; inclusive hgher education